Short-term Outcome of Low Birth Weight Preterm Infants with Necrotizing Enterocolitis: A Prospective Cohort Study - Pradyumna Pan (EL-Med-Pub, 2018)
Aim: The purpose of this study was to analyze the nature of the disease, the surgical procedures, complications, and survival of preterm infants with necrotizing enterocolitis (NEC) from two tertiary care referral neonatal intensive units in central India. Materials and Methods: A prospective study of a cohort of 110 preterm neonates with gestational age less than 36 weeks and weight less than 1600 g infants diagnosed to have NEC were followed for 90 days. All the neonates were born between January 2015 and December 2017 and treated at two neonatal intensive care units. Infants with sepsis, congenital gastrointestinal anomalies, major cardiac problems, and intraventricular hemorrhage were excluded. Results: Mean gestational age in this cohort was 32.40 ± 3.87 weeks, and the mean age of NEC onset was 13.04 ± 3.54 postnatal days. There were 39 neonates with Stage 1, 45 with Stage 2, and 26 with stage 3 NEC. Pneumoperitoneum, positive paracentesis and progressive clinical deterioration were the indications for laparotomy. The most common complications were sepsis 97/110 (88.18%). Post-operative complications occurred in 22 (84.61%) infants, wound infection in 19 (73.07%), intestinal stricture in 9 (34.61%), wound dehiscence in 7 (26.92%), stoma stenosis in 3 (11.53%), ileostomy prolapse in 2 (7.69%), and burst abdomen in 1 (3.84 %). The overall 90-day survival rate was 87.27% (96/110), and the post-operative survival rate was 46.15% (12/26). The age of gestation, weight, and extent of the disease were the main risk factor for mortality. Conclusion: The short-term outcomes for Stage 3 NEC were associated with high morbidity and mortality. The outlook for infants with Stage 1 and 2 NEC was favorable.